1984
DOI: 10.1111/j.1471-4159.1984.tb05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Identification of Colchicine‐Solubilized Regulatory Subunit from Rat Brain Adenylate Cyclase

Abstract: Five GTP binding proteins in rat cerebral cortex synaptic membranes were identified by photoaffinity labelling with [3H] or [32P](P3-azido-anilido)-P1-5' GTP (AAGTP). When AAGTP-treated membranes were incubated with colchicine or vinblastine and subsequently washed, a single AAGTP-labelled protein of 42 kD was released into the supernatant. About 30% of the total labelled 42-kD protein was released into supernatants from membranes pretreated with colchicine or vinblastine compared with 15% released from contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…6B). Previous studies have suggested that activated Gs␣ can be released from the plasma membrane into the cytosol; these results are certainly consistent with those observations (Rasenick et al, 1984;Ransas et al, 1989;Levis and Bourne, 1992). Furthermore, the distribution of Go␣ was not modified by antidepressant treatment (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…6B). Previous studies have suggested that activated Gs␣ can be released from the plasma membrane into the cytosol; these results are certainly consistent with those observations (Rasenick et al, 1984;Ransas et al, 1989;Levis and Bourne, 1992). Furthermore, the distribution of Go␣ was not modified by antidepressant treatment (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies, using cell fractionation or observations of fixed cells, have suggested that activated G␣ s may be released from plasma membranes (Rasenick et al, 1984;Ransas et al, 1989;Levis and Bourne, 1992). In this study, cholera toxin-activated G␣ s -GFP was released from plasma membrane during the course of activation and were gradually distributed through the cytosol.…”
Section: Visualization Of a Fluorescent G Protein 357mentioning
confidence: 60%
“…Previous studies, using cell fractionation and immunocytochemical assays, suggested that activation by ␤ adrenergic agonist, cholera toxin or direct binding of a hydrolysis-resistant GTP analog resulted in G␣ s translocation from plasma membrane to cytoplasm (Rasenick et al, 1984;Ransas et al, 1989;Levis and Bourne, 1992). G␣ q/11 has also been reported to transiently translocate to plasma membrane of adrenal glomerulosa cells in response to stimulation by angiotensin II for 1 to 5 min (Cote et al, 1997).…”
mentioning
confidence: 99%
“…It is well established that treatment of cells with microtubule-disrupting agents like colchicine and vinblastine leads to an increase in G protein-mediated activation of adenylyl cyclase (Kennedy and Insel, 1979;Rasenick et al, 1981Rasenick et al, , 1984Leiber et al, 1993;Jasper et al, 1995;Nishigaki et al, 1998;Rudolph et al, 1979). These potential actions would allow the cAMP signal to be propagated after receptor desensitization mediated by antidepressant treatment (reviewed by Sulser, 1984).…”
Section: Discussionmentioning
confidence: 99%